Low Temperature Enhances Plant Immunity via Salicylic Acid Pathway Genes That Are Repressed by Ethylene . Issue 1 (6th November 2019) - Li, Zhan; Liu, Huimin; Ding, Zehong; Yan, Jiapei; Yu, Huiyun; Pan, Ronghui; Hu, Jin; Guan, Yajing; Hua, Jian
Abstract : Disease resistance to the pathogen Pseudomonas syringae in Arabidopsis is enhanced by a lower temperature via up-regulating multiple genes in the salicylic acid pathway that are repressed by ethylene. Abstract: Temperature has a large impact on plant immune responses. Earlier studies identified intracellular immune receptor nucleotide-binding leucine-rich repeat (NLR) genes and salicylic acid (SA) as targets of high-temperature inhibition of plant immunity. Here, we report that moderately low temperature enhances immunity to the bacterial pathogen Pseudomonas syringae in Arabidopsis ( Arabidopsis thaliana ). This enhancement is dependent on SA signaling and is accompanied by up-regulation of multiple SA biosynthesis and signaling genes at lower temperature. SA signaling is repressed by jasmonic acid and ethylene at both normal and low temperatures. The inhibition of SA biosynthesis by ethylene, while mainly through ISOCHORISMATE SYNTHASE1/SALICYLIC ACID-INDUCTION DEFICIENT2 ( ICS1 / SID2 ) at normal temperature, is through ENHANCED DISEASE SUSCEPTIBILITY5 ( EDS5 )/ SID1, ICS2, and ICS1/SID2 at lower temperature. The repression by ethylene is mediated by a direct regulation of the ethylene response transcription factor ETHYLENE INSENSITIVE3 (EIN3) on multiple SA biosynthesis and signaling genes. Thus, low temperature enhances the SA pathway to promote immunity and at the same time uses ethylene to repress multiple SA regulators to achieve fine-tuned immune responses.